EFEK MODERASI PROFITABILITAS TERHADAP HUBUNGAN ANTARA TANGGUNG JAWAB SOSIAL DAN NILAI PERUSAHAAN DI TENGAH KRISIS EKONOMI GLOBAL - Andi Ayu Frihatni (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2018)
The developing countries including Indonesia experienced slow economic growth because of Eurozone financial crisis at its peak of 2012. The aim of this research is to test the relationship between Corporate Social Responsibility (CSR) on firm value moderated by profitability in the middle of global crisis. This research sample consists of 35 manufacture firms with financial statements in the period of 2012. The analysis method of this research uses Moderated Regression Analysis (MRA). The result of research discloses that the mean of profitability generated by manufacture firms in the middle of global crisis is low. However, it moderates the relationship between CSR on the firm value. It indicates that profitability can strengthen the increase of CSR on the firm value. CSR could lead the increase of the firm value when the profitability was low.